Investigating CO2 concentration and occupancy in school classrooms at different stages in their life cycle. (4th March 2018) - Luther, Mark B.; Horan, Peter; Tokede, Olubukola
ABSTRACT: This study emanated from a project measuring the levels of CO2 in a range of school classrooms in Victoria, Australia. The primary purpose of this paper is to understand how classroom usage affects the rise and fall of CO2, so as provide an acceptable environment while saving energy. Our intention is to develop an understanding of the temporal and quantitative relationships of CO2 build-up, and what measures could better control this performance. A literature review precedes our indepth investigation of past classroom measurements. We investigated CO2 emissions in 24 classrooms in six different schools in Australia. The buildings are at different stages in their life cycle from new to 45 years of age. We found that the most important parameters in predicting carbon dioxide concentration in a school classroom during its occupancy period are the air change rate, carbon dioxide exhalation rate and the number of pupils respectively.